Recent advances in the genetics and innate immune cells of bullous pemphigoid - Yang, Xiaoli; Wei, Panling; Wang, Zaixing (Frontiers in Immunology, 2025)
Bullous pemphigoid (BP) is a common autoimmune subepidermal blistering disease that primarily affects elderly patients. The pathogenesis of BP is complex, involving genetic, immune, and environmental factors. Recent evidence suggests that multiple genomic regions, particularly within the human leukocyte antigen (HLA)-II region, influence susceptibility to BP. Genetically predisposed individuals may carry susceptibility alleles that modulate the immune system, leading to an elevated risk of developing BP when exposed to the appropriate environmental triggers. Here, the present review discusses the genetics of BP and the critical role of the innate immune system in BP pathogenesis, focusing on the composition of innate immune cells.